Copolymers of polyethers comprising carboxylate salts and polyether side chains of different lengths and their use in mineral binder compositions

By using medium-long chain alkoxylated ethylenically unsaturated alcohol copolymers as superplasticizers for mineral binder compositions, the mineral binder compositions in the prior art has been solved by maintaining and resisting initial slump expansion in the prior art. The lack of compressive strength achieves efficient bonding performance and long-term stability.

CN119486984APending Publication Date: 2025-02-18SIKA TECH AG
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380050777.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-12
Filing Date
2023-06-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing PCE type copolymers cannot effectively improve the retention and compressive strength of initial slump expansion in certain mineral binder compositions.

Method used

Copolymers derived from alkoxylated ethylenically unsaturated alcohols with medium chain lengths (20-60 alkylene oxide repeat units) and long chain lengths (65-150 alkylene oxide repeat units) are used as mineral bonds. Superplasticizer of the catalyst composition.

Benefits of technology

A high initial slump expansion of the mineral binder composition is achieved and its performance is maintained for a longer period of time while improving the compressive strength after curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119486984A_ABST
    Figure CN119486984A_ABST
Patent Text Reader

Abstract

The invention relates to a copolymer, in particular a dispersant for mineral binders, comprising or consisting of the following monomer units: (i) a monomer unit of general formula (I) A # imgabs0 # (ii) a monomer unit of general formula (II) B # imgabs1 # and (iii) a monomer unit of general formula (III) C # imgabs2 #. The invention also relates to the use of the aforementioned copolymer as a plasticizer for mineral binder compositions. In particular, it has been found that the copolymer of the invention results in a high initial slump spread of mineral binder compositions and maintains its high slump spread over an extended period of time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to copolymers comprising at least two polyethers of different chain lengths and a carboxylate moiety. The present invention also relates to the use of such copolymers as plasticizers for mineral binder compositions. In particular, it has been found that the copolymers of the present invention produce a high initial slump flow of the mineral binder composition and maintain their high slump flow over a longer period of time. Background Art

[0002] For many years, copolymers of polycarboxylic acids and alkoxylated ethylenically unsaturated alcohols have been known as dispersants for aqueous dispersions, particularly for aqueous dispersions of mineral binders. Such copolymers are generally referred to as polycarboxylate (polycarboxylate) ethers (PCEs). PCEs act as superplasticizers and reduce the water required to achieve a certain level of fluidity for a given uncured mineral binder composition. The reduction of water in a mineral binder composition, particularly in a cement composition, is desirable because it results in less separation of solid components in the uncured composition and results in an increased compressive strength of the cured composition.

[0003] WO2016 / 074984 (BASF SE) discloses PCEs which are copolymers with polyether side chains of different lengths, one of which is short (5-35 alkylene oxide repeating units) and the other significantly longer (45-150 alkylene oxide repeating units). In particular, WO2016 / 074984 relates to copolymers derived from alkoxylated hydroxybutyl vinyl ether monomers.

[0004] CN103483504 (Sichuan Tongzhou Chemical Technology Co., Ltd.) discloses a PCE containing a copolymer of two different alkenyl polyethers, the copolymer being derived from a mixture of ethoxylated methallyl alcohol and ethoxylated isoprenol and its preparation. In addition, the number of repeating units of the copolymer side chains may be 32-44 when there are units derived from ethoxylated methallyl alcohol, and 52-62 when there are units derived from ethoxylated isoprenol.

[0005] The PCE type copolymers disclosed in the prior art are not the best choice as plasticizers for mineral binder compositions in all cases. One reason is that mineral binder compositions have large variations in possible components. Different mineral binders used, different aggregates used, different mixing ratios of components, etc. may require different copolymers as plasticizers. This is especially true in the case of more widespread use of manufactured sand and high-alkali concrete. Another reason is that many PCE type copolymers lead to a reduced development of compressive strength of the cured mineral binder composition, and even to a lower ultimate compressive strength. Lower compressive strength is generally not desired. Therefore, there is a need for improved PCE type copolymers to influence the water demand and / or rheology of the mineral binder composition. Summary of the invention

[0006] One object of the present invention is to provide a PCE type copolymer suitable as a superplasticizer for a mineral binder composition, in particular a cement binder composition.

[0007] (i) a high initial slump flow of the mineral binder composition should be achieved at a given mixing ratio with water, and / or

[0008] (ii) a minimum slump flow loss over time for a given mineral binder composition mixed with water should be achieved, and / or

[0009] (iii) should result in a higher compressive strength of the cured mineral binder composition compared to the same mineral binder composition with PCE-type copolymers of the prior art.

[0010] It has surprisingly been found that the copolymers according to claim 1 can solve one or more of these objects.

[0011] In particular, it has been found that copolymers derived from a combination of alkoxylated ethylenically unsaturated alcohols having a medium chain length (20-60 alkylene oxide repeating units) and alkoxylated ethylenically unsaturated alcohols having a long chain length (65-150 alkylene oxide repeating units) lead to a high initial slump flow, good retention of the slump flow over time and increased compressive strength. This is particularly the case where the ethylenically unsaturated alcohol having a medium degree of alkoxylation (20-60 repeating units) is selected from vinyl alcohol, vinyl-4-hydroxybutanol, (meth)allyl alcohol or isoprene alcohol, and where the ethylenically unsaturated alcohol having a high degree of alkoxylation (65-150 repeating units) is selected from vinyl alcohol or vinyl-4-hydroxybutanol.

[0012] Further aspects of the invention are the subject matter of further independent claims. Preferred embodiments of the invention are the subject matter of the dependent claims.

[0013] Specific embodiments of the present invention

[0014] In a first aspect, the present invention relates to a copolymer, in particular a dispersant for a mineral binder, comprising or consisting of the following monomer units:

[0015] (i) Monomer unit A of general formula (I)

[0016]

[0017] in

[0018] R 0 is H or methyl, R 1 is H, C1-C20 alkyl, aralkyl or aryl,

[0019] A is an alkylene group having 2-4 C atoms,

[0020] x = 0, 1 or 2,

[0021] y = 0 or 1, and

[0022] n = 20-60, preferably 40-60;

[0023] (ii) Monomer unit B of general formula (II)

[0024]

[0025] Where R 2 is H, C1-C20 alkyl, aralkyl or aryl,

[0026] A is an alkylene group having 2-4 C atoms,

[0027] o = 0 or 1, and

[0028] p = 65-150, preferably 120-140; and

[0029] (iii) Monomer unit C of general formula (III)

[0030]

[0031] Among them, independently of each other,

[0032] R u is H or methyl,

[0033] R v is H or COOM,

[0034] M is selected from H, alkali metal, alkaline earth metal, ammonium or an organic ammonium group,

[0035] and wherein the * in formulas (I), (I) and (III) describes the binding site into the polymer chain.

[0036] The copolymer of the present invention can be obtained by copolymerization of the following monomers:

[0037] (i) Monomer Aa of general formula (Ia)

[0038]

[0039] R 0 is H or methyl, R 1 is H, C1-C20 alkyl, aralkyl or aryl,

[0040] A is an alkylene group having 2-4 C atoms,

[0041] x=0, 1 or 2, y=0 or 1, and n=20-60, preferably 40-60;

[0042] (ii) Monomer Bb of general formula (IIa)

[0043]

[0044] in

[0045] R 2 is H, C1-C20 alkyl, aralkyl or aryl,

[0046] A is an alkylene group having 2-4 C atoms,

[0047] o = 0 or 1, and

[0048] p = 65-150, preferably 120-140; and

[0049] (iii) Monomer Cc of formula (IIIa)

[0050]

[0051] Among them, independently of each other,

[0052] R u is H or methyl,

[0053] R v is H or COOM,

[0054] M is selected from H, alkali metal, alkaline earth metal, ammonium or an organic ammonium group.

[0055] Suitable methods for preparing the copolymers of the present invention by copolymerization are known to those skilled in the art. In particular, copolymerization is a free radical polymerization method of different monomers. Suitable conditions for free radical polymerization methods are disclosed, for example, in Example 1-1 of EP 1103570 (Nippon Shokubai Chem Ind) or in Example 1 of WO 2012 / 084954 (Sika Technology AG). However, other methods of free radical polymerization are also suitable.

[0056] According to some embodiments, the copolymerization is carried out in the presence of an initiator for free radical polymerization at a reaction temperature of 10° C. to 50° C., preferably 15° C. to 35° C. The term "initiator for free radical polymerization" or "free radical initiator" in this document is defined as a compound described as an initiator in CD Rompp Chemie Lexikon, 9th edition, version 1.0, Georg Thieme Verlag, Stuttgart 1995, which is suitable for free radical polymerization. In particular, the copolymerization is carried out in the presence of a mixture of iron (II) sulfate, hypophosphite, hydrogen peroxide and sodium hydroxymethane sulfoxylate.

[0057] The copolymers of the present invention may be statistical copolymers or have a block or gradient arrangement of the monomers.

[0058] The monomer units A of the general formula (I) are preferably derived from ethoxylated, propoxylated and / or butoxylated vinyl alcohol, allyl alcohol, methallyl alcohol, isoprene alcohol and 4-hydroxybutyl vinyl ether. The monomer units of the general formula (I) may only carry ethylene oxide groups, or only carry propylene oxide groups, or only carry butylene oxide groups. It is also possible that the monomer units A of the general formula (I) carry a mixture of ethylene oxide groups, propylene oxide groups and / or butylene oxide groups, for example a mixture of ethylene oxide and propylene oxide groups or a mixture of ethylene oxide and butylene oxide groups.

[0059] Suitable monomer units B of the general formula (II) are preferably derived from ethoxylated, propoxylated and / or butoxylated vinyl alcohol and 4-hydroxybutyl vinyl ether. The monomer units B of the general formula (II) may carry only ethylene oxide groups, only propylene oxide groups, or only butylene oxide groups. It is also possible that the monomer units B of the general formula (II) carry a mixture of ethylene oxide groups, propylene oxide groups and / or butylene oxide groups, for example a mixture of ethylene oxide and propylene oxide groups or a mixture of ethylene oxide and butylene oxide groups.

[0060] According to a preferred embodiment, in the copolymers of the invention, at least 66 mol %, preferably at least 75 mol %, more preferably at least 90 mol %, in particular at least 99 mol % of the alkylene groups A in the general formulae (I) and (II) are ethylene groups.

[0061] Particularly preferably, in this context, the monomer units A of the general formula (I) are derived from ethoxylated vinyl alcohol or ethoxylated methallyl alcohol having a degree of ethoxylation of 40 to 60.

[0062] Particularly preferably, in this context, the monomer units B of the general formula (II) are derived from ethoxylated vinyl alcohol or ethoxylated 4-hydroxybutyl vinyl ether having a degree of ethoxylation of 120 to 140.

[0063] Suitable monomer units C of the general formula (III) are derived from acrylic acid and methacrylic acid and the salts thereof with alkali metal, alkaline earth metal, ammonium or organic ammonium groups.

[0064] Therefore, according to the embodiment, suitable monomer Aa is ethoxylated, propoxylated and / or butoxylated vinyl alcohol, allyl alcohol, methallyl alcohol, isoprenol and 4-hydroxybutyl vinyl ether, suitable monomer Bb is ethoxylated, propoxylated and / or butoxylated vinyl alcohol and 4-hydroxybutyl vinyl ether, and suitable monomer Cc is acrylic acid, methacrylic acid and / or maleic acid and salts of alkali metal, alkaline earth metal, ammonium or organic ammonium groups thereof. Of course, mixtures of two or more different acids can also be used as monomer Cc. According to the embodiment, monomer Cc is acrylic acid. According to other embodiments, monomer Cc is methacrylic acid. According to other embodiments, monomer Cc is maleic acid. According to other embodiments, monomer Cc is a mixture of acrylic acid and methacrylic acid. According to other embodiments, monomer Cc is a mixture of acrylic acid and maleic acid. According to other embodiments, monomer Cc is a mixture of methacrylic acid and maleic acid. According to other embodiments, monomer Cc is a mixture of acrylic acid, methacrylic acid and maleic acid. According to other embodiments, monomer Cc is a mixture of acrylic acid, methacrylic acid and maleic acid. According to other embodiments, monomer Cc is a mixture of acrylic acid, methacrylic acid and maleic acid.

[0065] According to other embodiments, the copolymers of the invention are characterized in that in the general structures (I) to (III), R 0 is methyl, R 1 and R 2 is H, A is ethylene; R u is H or methyl, R v is H or COOM, M is selected from H, alkali metal, alkaline earth metal or organic ammonium group, x=1, y=0, n=20-40, o=0 or 1, and p=65-140.

[0066] According to an embodiment, the copolymers of the present invention are characterized in that in the general structures (I) to (III), R 0is methyl, R 1 and R 2 is H, A is ethylene; R u is H or methyl, R v is H or COOM, M is selected from H, alkali metal, alkaline earth metal or organic ammonium group, x=1, y=0, n=40-60, o=0 or 1, and p=65-140.

[0067] According to other embodiments, the copolymers of the invention are characterized in that in the general structures (I) to (III), R 0 , R 1 and R 2 is H, A is ethylene; R u is H or methyl, R v is H or COOM, M is selected from H, alkali metal, alkaline earth metal or organic ammonium group, x=0, y=0 or 1, n=20-40, o=0 or 1, and p=65-140.

[0068] According to other embodiments, the copolymers of the invention are characterized in that in the general structures (I) to (III), R 0 , R 1 and R 2 is H, A is ethylene; R u is H or methyl, R v is H or COOM, M is selected from H, alkali metal, alkaline earth metal or organic ammonium group, x=0, y=0 or 1, n=40-60, o=0 or 1, and p=65-140.

[0069] The molar ratio of the monomer units of formula (I), (II), and (III) in the copolymer of the present invention can be expressed as a molar ratio of a:b:c, wherein a shall mean the molar fraction of monomer unit A of formula (I), b shall mean the molar fraction of monomer unit B of formula (II), and c shall mean the molar fraction of monomer unit C of formula (III).

[0070] According to an embodiment, the copolymer of the invention is characterized by a molar ratio a:b:c in the range of 0.01-0.9:0.9-0.01:1, preferably in the range of 0.04-0.5:0.5-0.06:1, in particular in the range of 0.03-0.08:0.09-0.12:1.

[0071] It is generally preferred that the molar ratio of monomer unit C is higher than the molar ratio of monomer unit A and / or monomer unit B. According to certain embodiments, the copolymer of the present invention is characterized in that the proportion of monomer unit C relative to all monomer units constituting the copolymer is 50-99 mol%, preferably 66-99 mol%, especially 75-99 mol%.

[0072] According to an embodiment, in the copolymer of the present invention, the molar ratio of monomer units A to monomer units B is greater than 0.1, preferably greater than 0.5, more preferably greater than 1, and especially greater than 3.

[0073] The molecular weight M of the copolymer of the present invention is w It can be measured by GPC using PEG as a standard and may be in the range of 5000-200000 g / mol, preferably 10000-150000 g / mol.

[0074] Optionally, the copolymers according to the invention may comprise further monomer units different from the monomer units A, B or C. According to an embodiment, the copolymers according to the invention may additionally comprise monomer units derived from monomers selected from the group consisting of esters of (meth)acrylic acid, in particular hydroxyalkyl (meth)acrylic acid esters such as 2-hydroxyethyl acrylate or 3-hydroxypropyl acrylate, (meth)acrylamide and its alkylamides, 2-acrylamido-2-methylpropanesulfonic acid, alkylene phosphates or alkylene phosphonates, in particular vinyl phosphate, N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone, N-vinylcaprolactam, (meth)allyl alcohol, hydroxyvinyl ethyl ether, hydroxyvinyl propyl ether, hydroxyvinyl butyl ether, 3-methyl-3-butene-1-ol, styrene, and / or butadiene.

[0075] In the case of the presence of the above-mentioned other monomer units, the molar ratio of the above-mentioned other monomer units relative to all the monomer units of the copolymer is preferably not higher than 33 mol%, more preferably not higher than 25 mol%. It is generally preferred that the copolymer of the present invention substantially does not contain any other monomer units other than the monomer units A, B and C. It is particularly preferred that the copolymer of the present invention consists of monomer units A, B and C.

[0076] According to an embodiment, the copolymer of the present invention is in the form of a dispersion or solution in a liquid, preferably in water. Such a dispersion or solution in a liquid, preferably in water, can be obtained by copolymerizing the corresponding monomers directly in a liquid, preferably directly in water. The copolymer of the present invention can also be dispersed or dissolved in a liquid, preferably in water, to obtain a copolymer dispersion or solution.

[0077] According to other embodiments, the copolymer of the present invention is solid at 25°C and 1023 mbar. The solid state is preferably a free-flowing powder or flakes. The solid copolymer may be particularly useful where the copolymer is to be mixed with other dry ingredients to form dry concrete or dry mortar. If the copolymer of the present invention is used therein in solid form, the storage life of such dry concrete or dry mortar may be improved.

[0078] The method for preparing the copolymer of the present invention in solid form is not particularly limited and is known per se to the person skilled in the art. Such methods include spray drying, oven drying, flaking, etc. of a dispersion or solution of the copolymer in a liquid.

[0079] In a second aspect, the present invention relates to the use of a copolymer as described above as an admixture in a mineral binder composition.

[0080] All embodiments described above also apply to this aspect.

[0081] A mineral binder composition herein is a composition comprising at least one mineral binder. The mineral binder is in particular a hydraulic binder (e.g. cement or hydraulic lime), a latent hydraulic binder (e.g. slag), a pozzolanic binder (e.g. fly ash, clay) or a non-hydraulic binder (e.g. gypsum plaster or slaked lime).

[0082] According to an embodiment, the mineral binder composition comprises a hydraulic binder, preferably cement. Particularly preferred is a cement having a cement clinker content of ≥35% by weight. In particular, the cement is a cement of type CEM I, II, III, IV or V according to standard EN 197-1 or a calcium aluminate cement or calcium sulphoaluminate cement according to standard EN 14647: 2006-01 or a mixture thereof. The proportion of hydraulic binder in the total mineral binder is advantageously at least 5% by weight, in particular at least 20% by weight, preferably at least 35% by weight, in particular at least 65% by weight. In another advantageous embodiment, the mineral binder comprises at least 95% by weight of hydraulic binder, in particular cement clinker.

[0083] In an advantageous embodiment, the cement further contains up to 40w%, preferably up to 35w%, in particular up to 20w% calcium sulfate, each based on the total dry weight of the cement. The calcium sulfate may be present in the form of calcium sulfate hemihydrate, calcium sulfate dihydrate and / or anhydrite.

[0084] According to a further embodiment, the mineral binder composition comprises other binders in addition to or instead of the hydraulic binder. These are in particular latent hydraulic binders and / or pozzolanic binders. Suitable latent hydraulic and / or pozzolanic binders are, for example, slag, clay, in particular calcined clay, fly ash, silica dust, silica fume, rice husk shale, burnt shale, volcanic ash and pumice. In an advantageous embodiment, the mineral binder contains 5-95% by weight, in particular 5-65% by weight, in particular 15-35% by weight of latent hydraulic and / or pozzolanic binders, relative to the total dry weight of the mineral binder.

[0085] The mineral binder composition of the present invention may also be based on calcium sulfate and / or lime as mineral binder. Calcium sulfate is meant to encompass any of anhydrite, α- and β-calcium sulfate hemihydrate and / or calcium sulfate dihydrate. Lime is meant to encompass any of hydraulic lime, air lime and / or natural hydraulic lime.

[0086] The copolymer of the invention is used in the mineral binder composition in an amount of 0.01-10w%, preferably 0.1-2w%, relative to the total weight of the mineral binder.

[0087] Therefore, in another aspect, the present invention also relates to a mineral binder composition comprising at least one mineral binder and 0.01 to 10% by weight, preferably 0.1 to 2% by weight, of a copolymer as described above, relative to the total weight of the mineral binder.

[0088] The mineral binder composition of the present invention may further comprise other ingredients, preferably, the other ingredients are selected from at least one of aggregates, fillers, additives and water.

[0089] The term aggregate as used in the context of the present invention refers to a mineral material which is non-reactive in the hydration reaction of the mineral binder.

[0090] Aggregate may be any aggregate commonly used in cementitious materials such as concrete, mortar, screed, render, grout, paint, putty, etc. Typical aggregates are, for example, rock, crushed stone, gravel, limestone, sand, recycled concrete, perlite or vermiculite.

[0091] In the context of the present invention, fillers are low-particle mineral additives that do not have cementitious properties. A typical filler is finely ground calcium carbonate.

[0092] The additive may be any additive commonly used in the concrete or mortar industry. Typical additives include plasticizers, thickeners, retarders, air entraining agents, deaerators, corrosion inhibitors, fibers, expansion-generating additives, pigments, strength enhancers, waterproofing additives, alkali-aggregate reaction inhibitors, chromate reducing agents and / or biocides.

[0093] According to an embodiment, the mineral binder composition of the invention is characterized in that it additionally comprises at least one of aggregates, fillers, additives and water.

[0094] The copolymers of the invention have the effect of increasing the initial slump flow and / or maintaining the slump flow of the mineral binder composition over a long period of time. The slump flow can be measured according to standard EN 12350-5.

[0095] In particular, the slump flow of a mineral binder composition comprising the copolymer of the invention is initially increased and / or maintained over a longer period of time compared to an identical mineral binder composition but comprising a polycarboxylate ether type copolymer not according to the invention. Thus, the copolymer of the invention is used as an admixture to a mineral binder composition to increase the initial slump flow and / or to increase the maintenance of the slump flow over time.

[0096] Therefore, the present invention also relates to a method for increasing the slump flow of a mineral binder composition, the method comprising the following steps:

[0097] (i) providing a mineral binder or a mineral binder composition,

[0098] (ii) providing a copolymer as described above, and

[0099] (iii) mixing the copolymer with a mineral binder or a mineral binder combination.

[0100] The use of the mineral binder composition of the present invention is not particularly limited. Generally, the mineral binder composition of the present invention can be used as concrete, mortar, screed, plaster, cement slurry, adhesive, waterproof membrane, cushion or water plug.

[0101] Therefore, in another aspect, the present invention also relates to the use of a mineral binder composition as described above as concrete, mortar, screed, render, plaster, grout, adhesive, waterproofing membrane, underlayment or water plug. Example

[0102] Preparation of copolymer CP-1

[0103] The copolymer was prepared by free radical polymerization. Therefore, 500 g of methallyl polyethylene glycol (OH-terminated, M w =2400g / mol), 53g of acrylic acid and 500g of water. 1.25g of 10% iron (II) sulfate * 7H2O aqueous solution and 1.7g of sodium hypophosphite were added. The mixture was heated to 35°C, and then 8.5g of 30% hydrogen peroxide aqueous solution and 3.5g of 5% hydroxymethane sodium sulfoxylate aqueous solution were slowly added dropwise. After the addition was completed, the reaction temperature was maintained at 40°C for 120 minutes. The resulting mixture was cooled to below 30°C and neutralized with NaOH. A transparent viscous solution of polymer CP-1 was obtained. Polymer CP-1 is a comparative polymer and is not a polymer described in the present invention.

[0104] Preparation of copolymer CP-2

[0105] Copolymer CP-2 was prepared in the same manner as copolymer CP-1, except that 500 g of ethyleneoxybutyl polyethylene glycol (OH-terminated, M w =6000g / mol) replaces 500g methallyl polyethylene glycol (OH terminated, M w =2400 g / mol). A transparent viscous solution of polymer CP-2 was obtained. Polymer CP-2 is a comparative polymer and is not a polymer according to the present invention.

[0106] Preparation of copolymer CP-3

[0107] Copolymer CP-3 was prepared in the same manner as copolymer CP-1, except that 38 parts by mass of ethyleneoxybutyl polyethylene glycol (OH-terminated, M w =3000g / mol) and 62 parts by mass of ethyleneoxybutyl polyethylene glycol (OH-terminated, M w =600g / mol) to replace 500g of methallyl polyethylene glycol (OH-terminated, M w =2400 g / mol). A transparent viscous solution of polymer CP-3 was obtained. Polymer CP-3 is a comparative polymer and is not a polymer according to the present invention.

[0108] Preparation of copolymer CP-4

[0109] Copolymer CP-4 was prepared in the same manner as copolymer CP-1, except that 736 g of ethyleneoxybutyl polyethylene glycol (OH-terminated, block copolymer M w =3000g / mol) replaces 500g methallyl polyethylene glycol (OH terminated, M w =2400 g / mol). A transparent viscous solution of polymer CP-4 was obtained. Polymer CP-4 is a comparative polymer and is not a polymer according to the present invention.

[0110] Preparation of copolymer CP-5

[0111] Copolymer CP-5 was prepared in the same manner as copolymer CP-1, except that 20 parts by weight of ethyleneoxybutyl polyethylene glycol (OH-terminated, M w =3000 g / mol) and 80 parts by weight of ethyleneoxybutyl polyethylene glycol (OH-terminated, molecular weight: M w =6000g / mol) mixture 500g replaces 500g methallyl polyethylene glycol (OH terminated, M w =2400 g / mol). A clear, viscous solution of polymer P-5 was obtained, which is a comparative polymer and not a polymer according to the invention.

[0112] Preparation of copolymer P-1

[0113] Copolymer P-1 was prepared in the same manner as copolymer CP-1, except that 80 parts by weight of methallyl polyethylene glycol (OH-terminated, M w =2400 g / mol) and 20 parts by weight of ethyleneoxybutyl polyethylene glycol (OH terminated, M w =3000g / mol) to replace 500g of methallyl polyethylene glycol (OH-terminated, M w =2400 g / mol). A transparent viscous solution of polymer P-1 was obtained. Polymer P-1 is the polymer described in the present invention.

[0114] Preparation of copolymer P-2

[0115] Copolymer P-2 was prepared in the same manner as copolymer CP-1, except that 50 parts by weight of methallyl polyethylene glycol (OH-terminated, M w =2400 g / mol) and 50 parts by weight of ethyleneoxybutyl polyethylene glycol (OH terminated, M w =3000g / mol) to replace 500g of methallyl polyethylene glycol (OH-terminated, M w =2400 g / mol). A transparent viscous solution of polymer P-2 was obtained. Polymer P-2 is the polymer described in the present invention.

[0116] Preparation of copolymer P-3

[0117] Copolymer P-3 was prepared in the same manner as copolymer CP-1, except that 20 parts by weight of methallyl polyethylene glycol (OH-terminated, M w =2400 g / mol) and 80 parts by weight of ethyleneoxybutyl polyethylene glycol (OH terminated, M w =6000g / mol) instead of 500g methallyl polyethylene glycol (OH terminated, M w =2400 g / mol). A transparent viscous solution of polymer P-3 was obtained. Polymer P-3 is the polymer described in the present invention.

[0118] Preparation of copolymer P-4

[0119] Copolymer P-4 was prepared in the same manner as copolymer CP-1, except that 15 parts by weight of ethyleneoxybutyl polyethylene glycol (OH-terminated, M w =6000 g / mol) and 85 parts by weight of isoprenyl polyethylene glycol (OH terminated, M w=2400g / mol) instead of 500g methallyl polyethylene glycol (OH terminated, M w =2400 g / mol). A transparent viscous solution of polymer P-4 was obtained. Polymer P-4 is the polymer described in the present invention.

[0120] Preparation of copolymer P-5

[0121] Copolymer P-5 was prepared in the same manner as copolymer CP-1, except that 25 parts by weight of ethyleneoxybutyl polyethylene glycol (OH-terminated, M w =3000 g / mol) and 75 parts by weight of isoprenyl polyethylene glycol (OH terminated, M w =2400g / mol) instead of 500g methallyl polyethylene glycol (OH terminated, M w =2400 g / mol). A transparent viscous solution of polymer P-5 was obtained. Polymer P-5 is the polymer described in the present invention.

[0122] Preparation of test mortar

[0123] Mortars C1-C5 and E1-E5 were prepared by dry mixing 750 g of cement (CEM I 52.5R from Vigier), 141 g of limestone filler, 738 g of sand (0-1 mm), 1107 g of sand (1-4 mm) and 1154 g of sand (4-8 mm) on a Hobart mixer at 25° C. for 1 minute. Then, the corresponding copolymers and water shown in Table 1 below were added within 30 seconds. In all cases, the amount of copolymer added was 1 w% relative to the cement, wherein 1 w% was relative to the dry matter of the aqueous polymer solution, i.e. the actual amount of the corresponding copolymer added. The amount of water added was such that the weight ratio of water to cement (w / c ratio) was 0.39. The amount of water added together with the aqueous copolymer solution was also calculated for this w / c ratio. Mixing was then continued for 2.5 minutes. Mortar compositions C1-C5 are comparative and not according to the invention, while mortar compositions E1-E5 are according to the invention.

[0124] The copolymers tested had different ratios of monomer units A, B and C (different molar ratios a:b:c). However, in all cases, the charge density of the copolymers tested was 1.3. The charge density of the copolymers was calculated from the respective molar ratios a:b:c and the molecular weight as mol COOH groups per gram of polymer.

[0125] The slump flow (abbreviated SF in Table 1) of each cement paste was measured according to EN 12350-5 after the times indicated in Table 1. The cement paste was mixed for a further 30 seconds before the measurement.

[0126] The compressive strength (abbreviated CS in Table 1) was measured according to EN 12190 on a 4×4×16 cm prism after the times indicated in Table 1 below.

[0127] The solidification time is derived from the cumulative heat flow curve determined by integrating the heat flow curve measured in the isothermal process described in standard ASTM C1702-17 using the instrument i-CAL 8000 from Calmetrix. The solidification time is the time for the cumulative heat flow curve to reach a plateau.

[0128] Table 1 below shows the results.

[0129] Table 1: Test results

[0130] Example C1 C2 C3 C4 C5 E1 E2 E3 E4 E5 Copolymer CP-1 CP-2 CP-3 CP-4 CP-5 P-1 P-2 P-3 P-4 P-6 SF@0min[mm] 208 187 145 175 216 238 207 216 214 222 SF@30min[mm] 205 212 nm nm 231 241 217 213 nm nm SF@60min[mm] 195 197 nm nm 224 229 204 205 nm nm △SF* -6% +5% nm nm +4% -4% -1% -5% nm nm Solidification time [h] 10.5 nm nm nm 7.6 8.8 8.8 8.2 nm nm CS@8h[MPa] 2.6 12.5 2.1 6.7 8.0 4.6 4.5 7.5 5.8 7.1

[0131] nm: Not measured

[0132] **△SF: Slump spread over time, calculated as follows:

[0133] [(“Slump expansion 0 minutes” - “Slump expansion 60 minutes”) / “Slump expansion 0 minutes”)]*-100

[0134] Negative values ​​are the loss of slump spread over time.

[0135] Positive values ​​indicate that the slump propagation increases with time.

[0136] The results of Table 1 show that the polymers of the prior art lead to a satisfactory initial slump expansion, but show a significant slump loss over time, and also show a relatively low compressive strength (see Example C1). The polymers of the prior art with longer side chains can lead to an increase in compressive strength, but also show a reduced initial slump expansion (see Examples C2 and C4 vs. C1). Compared with the copolymers of the prior art, the copolymers of the present invention are able to increase the initial slump expansion while maintaining a relatively high compressive strength (see Examples E1 to E5). At the same time, when the copolymers of the present invention are used, the loss of slump expansion over time is at a level that is completely acceptable in practical applications and is lower than the copolymers of the prior art. The comparative copolymer CP-4 shows an increase in slump expansion over time, which is generally undesirable. Copolymers whose short side chains do not have sufficient length (e.g., only about 13 EO units in CP-3) do not lead to satisfactory slump expansion and early strength (see Example C3).

Claims

1. A copolymer, in particular for use as a dispersant for mineral binders, comprising or consisting of the following monomer units: (i) Monomer unit A of general formula (I) in R 0 is H or methyl, R 1 is H, C1-C20 alkyl, aralkyl or aryl, A is an alkylene group having 2-4 C atoms, x = 0, 1 or 2, y = 0 or 1, and n = 20-60, preferably 40-60; (ii) Monomer unit B of general formula (II) Where R 2 is H, C1-C20 alkyl, aralkyl or aryl, A is an alkylene group having 2-4 C atoms, o = 0 or 1, and p = 65-150, preferably 120-140; and (iii) Monomer unit C of general formula (III) Among them, independently of each other, R u is H or methyl, R v is H or COOM, M is selected from H, alkali metal, alkaline earth metal, ammonium or an organic ammonium group, and wherein the * in formulas (I), (I) and (III) describes the binding site into the polymer chain.

2. The copolymer according to claim 1, characterized in that In the general structures (I) to (III), R 0 is methyl, R 1 and R 2 is H, A is ethylene; R u is H or methyl, R v is H or COOM, M is selected from H, alkali metal, alkaline earth metal or organic ammonium group, x=1, y=0, n=40-60, o=0 or 1, and p=65-140.

3. The copolymer according to claim 1, characterized in that In the general structures (I) to (III), R 0 , R 1 and R 2 is H, A is ethylene; R u is H or methyl, R v is H or COOM, M is selected from H, alkali metal, alkaline earth metal or organic ammonium group, x=0, y=0 or 1, n=40-60, o=0 or 1, and p=65-140.

4. The copolymer according to claim 1, wherein at least 66 mol%, preferably at least 75 mol%, more preferably at least 90 mol%, especially at least 99 mol% of the alkylene groups A in the general formula (I) and (II) are ethylene groups.

5. The copolymer according to any one of the preceding claims, characterized in that The molar ratio of the monomer units a:b:c is in the range of 0.01-0.9:0.9-0.01:1, preferably in the range of 0.04-0.5:0.5-0.06:1, especially in the range of 0.03-0.08:0.09-0.12:

1.

6. The copolymer according to any one of the preceding claims, characterized in that The copolymers further comprise units derived from monomers selected from esters of (meth)acrylic acid, in particular hydroxyalkyl (meth)acrylic acid esters such as 2-hydroxyethyl acrylate or 3-hydroxypropyl acrylate, (meth)acrylamide and its alkylamides, 2-acrylamido-2-methylpropanesulfonic acid, alkylene phosphates or phosphonates, in particular vinyl phosphate, N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone, N-vinylcaprolactam, (meth)allyl alcohol, hydroxyvinyl ethyl ether, hydroxyvinyl propyl ether, hydroxyvinyl butyl ether, 3-methyl-3-butene-1-ol, styrene and / or butadiene.

7. The copolymer according to any one of claims 1 to 6, characterized in that The copolymer is in powder form.

8. The copolymer according to any one of claims 1 to 6, characterized in that The copolymer is in the form of a dispersion or solution in a liquid, preferably water.

9. The copolymer according to any one of the preceding claims, characterized in that The ratio of the monomer unit c to all monomers constituting the copolymer is 50 to 99 mol %, preferably 66 to 99 mol %, and particularly 75 to 99 mol %.

10. The copolymer according to any one of the preceding claims, characterized in that The molar ratio of monomer unit a to monomer unit b is greater than 0.1, preferably greater than 0.5, more preferably greater than 1, and especially greater than 3.

11. Use of a copolymer according to any one of claims 1 to 10 as an admixture in a mineral binder composition.

12. A mineral binder composition comprising at least one mineral binder and 0.01% to 10% by weight, preferably 0.1% to 2% by weight, of a copolymer according to any one of claims 1 to 10, relative to the total weight of the mineral binder.

13. The mineral binder composition according to claim 12, characterized in that The mineral binder composition additionally comprises at least one of aggregate, filler, additives and water.

14. Use of the mineral binder composition according to any one of claims 12 to 13 as concrete, mortar, screed, render, plaster, grout, adhesive, waterproof membrane, underlayment or water plug.

Citation Information

Patent Citations

  • Copolymer for cement admixtures and its production process and use

    EP1103570A2

  • Polymer made from maleic acid, allyl ether, and vinyl acetate, production of said polymer, and use of said polymer

    WO2012084954A1

  • Polymer having polyether side chains

    WO2016074984A1